Stone Attenuation and Skin-to-Stone Distance on Computed Tomography Predict the Performance of Shock Wave Lithotripsy in Renal Stone Disease (Bangladesh Medical Journal, 2025)
Shock wave lithotripsy (SWL) is a noninvasive, safe, and effective method of treating renal stones.  The overall stone-free rate (SFR) varies greatly depending on stone location and size. Failure to disintegrate the stone results in unnecessary exposure to shock waves and radiation, as well as the need for alternative treatment procedures, which raises medical costs. Prior to treatment, it is critical to identify predictors of treatment success or failure in patients who are potential candidates for SWL. The purpose of this study is to determine if stone attenuation and skin-to-stone distance in computed tomography have the ability to predict the success of shock wave lithotripsy in renal stone disease. This prospective observational study was carried out in the Department of Urology at BSMMU's in collaboration with the Department of Radiology and Imaging from January to December 2023. Patients with renal stones who were scheduled for shock wave lithotripsy (SWL) were enrolled in this study after obtaining their consent. The history of these patients, including their drug and dietary histories, was recorded in detail. Each patient was given computed tomography to evaluate stone attenuation and skin-to-stone distance. After SWL Stone clearance rate was compared with stone attenuation and skin-to-stone distance. The statistical package for social sciences (SPSS) version 20.0 was used to analyze the data. Males were more prevalent than females, but the stone-free rate was higher in females, though this difference was not statistically significant. Younger patients experienced a higher stone-free rate, and patients with low BMI had better outcomes than those with high BMI. Stones were most abundant in the lower pole, followed by the pelvis, central, and upper pole. The stone-free rate was highest in the pelvis, followed by the central, lower pole, and upper pole. Stone-free status was more common among patients with smaller stones and lower stone attenuation, though these differences were not statistically significant. Patients with a shorter skin-to-stone distance had a significantly higher rate of stone extraction. Skin-to-stone distance more effectively predicts the success of SWL in renal stone disease than stone attenuation.Bangladesh Med J. 2024 Jan; 53(1): 12-17